Prevalence, source and severity of work-related injuries among ''foreign'' construction workers in a large Malaysian organisation: a cross-sectional study - Zerguine, Haroun; Mohd Tamrin, Shamsul Bahri; Jalaludin, Juliana (National Institute of Industrial Health, 2018)
Malaysian construction sector is regarded as critical in the field of health because of the high rates of accidents and fatalities. This research aimed to determine the prevalence, sources and severity of injuries and its association with commitment to safety among foreign construction workers. A cross-sectional study was conducted among 323 foreign construction workers from six construction projects of a large organization in Malaysia, using a simple random sampling method. Data was collected using a structured questionnaire to assess work-related injuries and safety commitment. The collected data was analysed by SPSS 22.0 using descriptive statistics and χ2 test. The prevalence of work-related injuries in a one year period was 22.6%, where most of the injuries were of moderate severity (39.7%) and falls from heights represented the main source (31.5%). The majority of the foreign construction workers had perceived between moderate and high safety commitment, which was significantly associated with work-related injuries. The results also showed a significant association of work-related injuries with the company's interest in Safety and Health, Safety and Health training, and safety equipment. Thus, the implementation of new procedures and providing relevant trainings and safety equipment; will lead to a decrease in injury rates in construction sites.